European landraces: on-farm conservation, management and use - Veteläinen, M.; Negri, V.; Maxted, N. (2009)
This technical bulletin first establishes the context of European landrace diversity conservation and use; it reviews how landrace inventories can be generated, using practical examples of such inventories for European countries; it then provides specific case studies of the on farm management of landraces; and exemplars of how landrace use has been and might be further promoted within a European agricultural context. The recent introduction of the Commission Directive 2008/62 EC on Conservation Varieties will impact European landrace diversity; this is discussed together with the development of diverse European and National policies to support the conservation and use of landraces in production systems for sustainable agriculture. The technical bulletin concludes with a discussion of why we still need landraces, the current conservation status of European landraces, a review of the threats to on farm management of landraces and the opportunities for future landrace cultivation. It concludes with a proposal for a European on farm conservation and landrace management strategy that will both ensure the systematic conservation landrace diversity and promote its sustainable use, thus helping to underpin European food security and well being.